2020
DOI: 10.1017/pasa.2020.34
|View full text |Cite
|
Sign up to set email alerts
|

ASKAP reveals giant radio halos in two merging SPT galaxy clusters

Abstract: Early science observations from the Australian Square Kilometre Array Pathfinder (ASKAP) have revealed clear signals of diffuse radio emission associated with two clusters detected by the South Pole Telescope via their Sunyaev Zel’dovich signal: SPT CLJ0553-3342 (MACS J0553.4-3342) and SPT CLJ0638-5358 (Abell S0592) are both high-mass lensing clusters that have undergone major mergers. To create science-fidelity images of the galaxy clusters, we performed direction-dependent (DD) calibration and imaging on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 99 publications
6
17
0
Order By: Relevance
“…We update this relation at GHz and GHz following (van Weeren et al, 2020, hereafter vW20). For this work, we incorporate the compiled literature sample of halos reported by C13 and Martinez Aviles et al (2016), halos in Abell S1121 and Abell 2811 reported by Duchesne et al (2021b), and new halos reported in the literature from 2017 (Parekh et al, 2017; Wilber et al, 2018; Cassano et al, 2019; Brzan et al 2019; Xie et al, 2020; HyeongHan et al, 2020; Giovannini et al, 2020; Wilber et al, 2020; Hoeft et al, 2020; Hoang et al, 2021; Di Gennaro et al, 2020; van Weeren et al, 2020; Raja et al, 2020; Knowles et al, 2021; Raja et al, 2021), with the exception of the halo in ACT-CL J0528.8 –3927 reported by Knowles et al (2021) as its small size and coincidence with a radio-bright BCG suggests a mini-halo. For consistency, cluster masses are obtained from PSZ measurements where available (Planck Collaboration et al 2016c, with some masses obtained from the South Pole Telescope; Song et al, 2012; Reichardt et al, 2013), and only clusters with an SZ-derived mass are used.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We update this relation at GHz and GHz following (van Weeren et al, 2020, hereafter vW20). For this work, we incorporate the compiled literature sample of halos reported by C13 and Martinez Aviles et al (2016), halos in Abell S1121 and Abell 2811 reported by Duchesne et al (2021b), and new halos reported in the literature from 2017 (Parekh et al, 2017; Wilber et al, 2018; Cassano et al, 2019; Brzan et al 2019; Xie et al, 2020; HyeongHan et al, 2020; Giovannini et al, 2020; Wilber et al, 2020; Hoeft et al, 2020; Hoang et al, 2021; Di Gennaro et al, 2020; van Weeren et al, 2020; Raja et al, 2020; Knowles et al, 2021; Raja et al, 2021), with the exception of the halo in ACT-CL J0528.8 –3927 reported by Knowles et al (2021) as its small size and coincidence with a radio-bright BCG suggests a mini-halo. For consistency, cluster masses are obtained from PSZ measurements where available (Planck Collaboration et al 2016c, with some masses obtained from the South Pole Telescope; Song et al, 2012; Reichardt et al, 2013), and only clusters with an SZ-derived mass are used.…”
Section: Resultsmentioning
confidence: 98%
“…With the current generation of radio telescopes, telescope upgrades, increases in sensitivity, and low-frequency operation are helping to reveal a new population of radio halos (e.g. Duchesne et al, 2021b; Cassano et al, 2019; HyeongHan et al, 2020; Wilber et al, 2020; Di Gennaro et al, 2020; Hoeft et al, 2020; van Weeren et al, 2020; Knowles et al, 2021; Hodgson et al, 2021) and to clarify the nature of previously detected systems (e.g. Botteon et al, 2020c; Bonafede et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All but one of our detections are new, with the halo in ACT-CL J0638.7−5358 having been detected by ASKAP (Wilber et al 2020). We do not detect the full ASKAP halo emission in this system; however, we do resolve a peaked region in the halo that is morphologically aligned with the X-ray emission of the infalling subcluster seen in fig.…”
Section: Discussionmentioning
confidence: 47%
“…We note that our ACT-CL J0638.7−5358 radio halo, residing in the most massive of our clusters, lies at the edge of the scatter in the literature values, and in the region typically associated with ultrasteep spectrum sources. However, our power is likely underestimated due to missing flux, as described above, with Wilber et al (2020) quoting a halo power a factor of ∼2.8 higher, which would move it closer to the correlation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation